THE DIGITAL BANKING PROFITABILITY CHALLENGES: ARE THEY DIFFERENT BETWEEN CONVENTIONAL AND ISLAMIC BANKS? - Yunita, Patria (UI Scholars Hub, 2021)
This study aims to analyze the digital banking industry in uncertain global financial conditions. This analysis used binary logistic regression models, to predict the Indonesia commercial digital banking profitability performances in new normal life based on the analysis of digital banking performances in the second wave of global financial crisis 2017. The probability of bank profitability improvement as dependent variable. The Liquidity Risk, Bank Size, Bank Portfolio Risk, and E-Money transactions as independent variables. Fintech and Bank Type are used as control variables. The analysis period is 2015-2019, based on the time when the rapid progress of digital banking technology was adopted in Indonesia. Data obtained from 57 commercial bank annual reports, statistics of Bank Indonesia and The Financial Services Authority. By the Logit Regression Model, it is concluded that Liquidity Risk, Fintech and Bank Type do not statistically significant, while the Bank’s Portfolio Risk, E-Money transactions and Bank Size statistically significant influencing The Digital Banking Profitability Improvements. From the structural break analysis conducted at the level of the digital banking profitability, there is a difference in the time of